Uji Aktivitas Antibakteri dan Permeabilitas Membran Hibrid Nilon-TiO2 - wenny maulina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
Hybrid membranes from nylon and titanium dioxide (TiO2) were prepared using hydrogen chloride (HCl) as precursor and acetyl aceton as chelating agent in the casting solution by phase inversion methods. The aim of this study was investigated antibacterial effect and permeation flux due to the impact of TiO2 contents on the hybrid membranes. Among all the prepared membranes, nylon-TiO2 hybrid membranes with mass fraction 70wt%:30wt% exhibited the best antibacterial effect. Meanwhile, the additions of TiO2 were raised water and sodium chloride (NaCl) permeability from 0 to 40wt%.